Contralateral Metabolic Activation Related to Plastic Changes in the Spinal Cord after Peripheral Nerve Injury in Rats - Won, Ran (Neural Plast, 2015)
We have previously reported the crossed-withdrawal reflex in which the rats with nerve injury developed behavioral pain responses of the injured paw to stimuli applied to the contralateral uninjured paw. This reflex indicates that contralateral plastic changes may occur in the spinal cord after unilateral nerve injury. The present study was performed to elucidate the mechanisms and morphological correlates underlying the crossed-withdrawal reflex by using quantitative (14)C-2-deoxyglucose (2-DG) autoradiography which can examine metabolic activities and spatial patterns simultaneously. Under pentobarbital anesthesia, rats were subjected to unilateral nerve injury. Mechanical allodynia was tested for two weeks after nerve injury. After nerve injury, neuropathic pain behaviors developed progressively. The crossed-withdrawal reflex was observed at two weeks postoperatively. Contralateral enhancement of 2-DG uptake in the ventral horn of the spinal cord to electrical stimulation of the uninjured paw was observed. These results suggest that the facilitation of information processing from the uninjured side to the injured side may contribute to the crossed-withdrawal reflex by plastic changes in the spinal cord of nerve-injured rats.